2016
DOI: 10.1111/epi.13341
|View full text |Cite
|
Sign up to set email alerts
|

Preresection intraoperative electrocorticography (ECoG) abnormalities predict seizure‐onset zone and outcome in pediatric epilepsy surgery

Abstract: SUMMARYObjective: The predictive value of intraoperative electrocorticography (ECoG) in pediatric epilepsy surgery is unknown. In a population of children undergoing ECoG followed typically by invasive extraoperative monitoring (IEM) and resection, we aimed to determine the relationship between frequent ECoG abnormalities and the seizure onset zone and outcome after resection. Methods: We retrospectively identified 103 children with preresection ECoG of sufficient technical quality. ECoG records were scored ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The relationship between spike and seizure networks has been controversial for decades . Previous studies have shown that complete excision of regions generating spike discharges (ie, irritative zone) is correlated with seizure‐free outcomes, whereas others find that complete irritative zone resection is neither necessary nor sufficient to ensure favorable outcomes . Network‐based analysis of spike propagation is relatively understudied compared to the standard clinical approach, which emphasizes the spatial localization of spike discharges rather than spike coactivation between brain regions .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between spike and seizure networks has been controversial for decades . Previous studies have shown that complete excision of regions generating spike discharges (ie, irritative zone) is correlated with seizure‐free outcomes, whereas others find that complete irritative zone resection is neither necessary nor sufficient to ensure favorable outcomes . Network‐based analysis of spike propagation is relatively understudied compared to the standard clinical approach, which emphasizes the spatial localization of spike discharges rather than spike coactivation between brain regions .…”
Section: Discussionmentioning
confidence: 99%
“…Several epileptiform patterns may be recorded, including continuous or intermittent bursts of spike and wave and high‐frequency oscillations . Attenuation of beta activity or the presence of delta‐wave activity may indicate a higher likelihood of an epileptic focus that warrants electrode coverage .…”
Section: Implantation Techniquementioning
confidence: 99%
“…However, evidence supporting this interpretation of spike activity is inconclusive (3). Resection of the spiking region has been associated with improved surgical outcomes (4, 5), though for many patients, persistent postoperative spiking is compatible with seizure freedom (6). Spikes are routinely observed in regions beyond the neurologist-defined seizure onset zone (SOZ), and the localization of spikes to the SOZ varies tremendously between patients and across time (7).…”
Section: Introductionmentioning
confidence: 99%